The Results of Enrichment of Samples of Ore Deposits Eshlik Using the Traditional and Local SI Reagent (Eurasian Scientific Herald, 2022)
In job the results of study of material structure and enrichment of tests of ores of deposits Eshlik are given. As a result of the studies, recommended regimens for enrichment of ores were developed using a combination of a traditional collector and “CI” at a flow of 50% of the mixture of xantogenes and concentrates of higher quality were obtained